Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

if a=xy^(p-1),b=xy^(q-1) and c=xy^(r-1).prove that a^(o-r).b^(p).q^(p-q)=1

if a=xy^(p-1),b=xy^(q-1) and c=xy^(r-1).prove that a^(o-r).b^(p).q^(p-q)=1

Grade:9

1 Answers

Riddhish Bhalodia
askIITians Faculty 434 Points
6 years ago
I am pretty sure the you made a slight mistake in typing the question
you would have to prove
a^{q-r}b^{r-p}c^{p-q} = 1
so to do that just substitute the values of a b and c
we get
LHS = x^{q-r+r-p+p-q}y^{(p-1)(q-r) + (q-1)(r-p) + (r-1)(p-q)}
LHS = x^{0}y^{pq-pr-q+r+qr-pq-r+p+pr-qr-p+q} = x^0y^0 = 1 = RHS
hence proved

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free